Selective Lithiation–Expansion–Microexplosion Synthesis of Two-Dimensional Fluoride-Free Mxene - Sun, Zemin; Yuan, Mengwei; Lin, Liu; Yang, Han; Nan, Caiyun; Li, Huifeng; Sun, Genban; Yang, Xiaojing (ACS materials letters, 2019)
Two-dimensional MXene, a significant member of the two-dimensional family, has attracted much interest in physics, energy evolution, environmental science, and nanomedicine. However, the acute toxicity of fluoride-based synthetic procedures remains an impediment to large-scale fabrication and applications. It is an urgent need to develop an innocuous and effective protocol for MXene synthesis. Therefore, we developed a facile, rapid fluoride-free electrochemical etching strategy based on the selective corrosion of Al layers in titanium aluminum carbide (Ti3AlC2) in a traditional Li-ion battery system. On the basis of the intercalation–alloying–expansion–microexplosion mechanism, single- and few-layer fluoride-free Ti3C2T x (T = O or OH) were prepared. Furthermore, the fluoride-free Ti3C2T x exhibits excellent capability for a supercapacitor. This strategy provides a safe, green, and environmentally friendly way to realize the production of ultrathin MXene materials from MAX.